Implikasi Penetapan Suku Bunga Kredit bagi Nasabah Debitur - Ni Kadek Ayu Dea Novi Andini; I Nyoman Sujana; I Made Aditya Mantara Putra (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The banking sector, as an intermediary institution, plays a strategic role in the national economy. However, the absence of regulations that explicitly limit the maximum loan interest rate in legislation creates a legal vacuum that has the potential to harm borrowers and weaken legal protections. The research questions in this study are: (1) How are loan interest rates determined under positive law in Indonesia; (2) What legal protections are in place for customers against the risk of loss resulting from the misuse of loan interest rate setting. This study employs a normative legal research method using a legislative and conceptual approach, along with the collection of legal materials through a literature review. The research findings indicate that existing regulations, including Financial Services Authority Regulation No. 13 of 2024, only address the transparency of the Base Lending Rate without setting a maximum limit, thereby creating a regulatory gap. Legal protection for customers includes preventive legal protection through transparency and supervision, as well as repressive legal protection through dispute resolution mechanisms and the provision of compensation; however, its implementation remains suboptimal. Therefore, regulatory strengthening is necessary to ensure legal certainty and fair protection for debtor customers.